2022
DOI: 10.1039/d2sc01088g
|View full text |Cite
|
Sign up to set email alerts
|

Between imide, imidyl and nitrene – an imido iron complex in two oxidation states

Abstract: A pair of trigonal imido iron complexes ([Fe(NMes)L2]0,−) in two oxidation states is reported. The anionic complex K{crypt.222}[Fe(NMes)L2] is best described as an iron(ii) imide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 69 publications
7
27
0
1
Order By: Relevance
“…Overall, the Fe-N interactions are reminiscent of imido complexes where a formally iron(IV) complex was described as an iron(III) complex with a nitrenyl radical. [38][39][40][41][42][43][44][45][46][47][48] The amount of radical character on the N is similar to that in tris(phosphino)borane-supported FeNNMe2 complexes studied in detail by Peters. 31 However, in 5a we emphasize that the N radical is not the dominant configuration; rather, 5a can still be viewed as a formally iron(IV) complex with substantial covalency and an iron-nitrogen triple bond, as shown by the presence of two unoccupied orbitals with Fe-N p* character.…”
Section: Mechanistic Evaluation Using Computationssupporting
confidence: 66%
“…Overall, the Fe-N interactions are reminiscent of imido complexes where a formally iron(IV) complex was described as an iron(III) complex with a nitrenyl radical. [38][39][40][41][42][43][44][45][46][47][48] The amount of radical character on the N is similar to that in tris(phosphino)borane-supported FeNNMe2 complexes studied in detail by Peters. 31 However, in 5a we emphasize that the N radical is not the dominant configuration; rather, 5a can still be viewed as a formally iron(IV) complex with substantial covalency and an iron-nitrogen triple bond, as shown by the presence of two unoccupied orbitals with Fe-N p* character.…”
Section: Mechanistic Evaluation Using Computationssupporting
confidence: 66%
“…A high-spin three-coordinate Fe imidyl complex 2 was isolated and characterized. 71 Combined magnetic, spectroscopic, and computational (DFT, CASSCF, and CASCI) studies showed that 2 is an S = 2 Fe( iii ) imidyl complex, with an S = 5/2 ground state on Fe that is antiferromagnetically coupled to the imidyl radical on N. The reaction of 1 with AdN 3 afforded the intramolecular C–H amination product 3 , whereas the corresponding Fe imidyl intermediate ( 3′ ) could not be isolated. Quantum mechanical calculations shed light on the divergent reactivity and stability of 2 and 3′ .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fe(II,III) imido complexes have been synthesized by coordinating organic azides at low-valent iron precursors with concomitant release of N 2 . 41−43 Since then, several imido complexes with Fe(II,III) [8][9][10][11][12][13]44 �and fewer with Fe(IV) 2,45,46 �centers have been reported. In contrast, iron imido complexes in oxidation states +V and +VI remain exceedingly rare.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Accordingly, strong σ-donor ligands, such as carbenes, phosphines, and guanidinates, in trigonal, custom-tailored coordination environments have been used to stabilize this class of compounds. , Employing these ligands, mononuclear, terminal Fe­(IV) , and Fe­(V) nitrido complexes have been accessed via dinitrogen fixation or azide photolysis. Similarly, Fe­(II,III) imido complexes have been synthesized by coordinating organic azides at low-valent iron precursors with concomitant release of N 2 . Since then, several imido complexes with Fe­(II,III) , and fewer with Fe­(IV) ,, centers have been reported. In contrast, iron imido complexes in oxidation states +V and +VI remain exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%